Rancang Bangun Sistem Informasi Penerimaan Mahasiswa Baru Berbasis Web untuk Meningkatkan Efektivitas Proses Pendaftaran - Muhammad Yunus Rangkuti; Aditya Ramadhan; Kayla Fahira Dinia; Vayza Valensia Gabrella Wuntu (Jurnal Riset Informatika dan Inovasi, 2026)
The New Student Admission (PMB) process in many higher education institutions is still conducted manually or semi-digitally, resulting in various problems such as delays in data processing, recording errors, and low effectiveness in the registration process. This study aims to design and develop a web-based New Student Admission Information System (SPMB) that facilitates online registration for prospective students and assists universities in managing admission data in an integrated manner. The system development method used in this study is the Waterfall method, which consists of requirement analysis, system design, implementation, and testing stages. The result of this study is a web-based SPMB system capable of managing applicant data efficiently and simplifying the registration process. The developed system is expected to improve the effectiveness and efficiency of the new student admission process.